Pengaruh media budidaya yang berbeda terhadap kepadatan populasi cacing Tubifex (Tubifex sp.) - Frid Agustinus (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
The aim of this study was to determine the effect of different culture media on population density of Tubifex worms, so that we can find a good medium for the development Tubifex worms. This study uses a model of completely randomized design (RAL) with four treatments and three replications. Media treatment A using chicken manure, treatment B using the media pulp, treatment C using lettuce rotting media and media treatment D using chicken feed. Based on the research results can be concluded that the use of chicken manure as culture media gives a significant influence on the population density of Tubifex worms (Tubifex sp.) than other media. Key words : Population density, culture media, Tubifex worms.